Citocentrifugação e métodos convencionais na citologia uterina de éguas em estro e diestro - Jorge, M. L.N. [UNESP]; Orlandi, C. M.B.; Santana, A. E. [UNESP] (FapUNIFESP (SciELO), 2017)
The endometrial cytology consists in an efficient and practical method for the diagnosis of uterine disorders in mares, contributing for therapeutic conduct and prognostic evaluation regarding the females' fertility. Therefore, the aim of this study was to compare different techniques of material sampling for endometrial cytology in mares, in order to verify possible qualitative and quantitative differences in the practicality of implementation of this methodology. Twelve multiparous mares underwent an endometrial cytological exam, during estrus and diestrus, by means of a cytobrush and a low-volume uterine flush. With this test, no statistical difference was observed (P > 0.05) regarding the result of endometrial cytology between the evaluated techniques. However, in comparison to the estrous cycle's phases, a significant difference was verified (P < 0.05) on the average percentage of polymorphonuclear neutrophils: 8.07±2.80 in estrus and 1.55±0.28 in diestrus. Thus, we conclude that the studied techniques presented equally effective results for the detection of neutrophils in the cytological exam for both evaluated stages of the estrous cycle, whereas in estrus phase, the detection of a higher percentage of neutrophils allows a more precocious diagnostic and prognostic of endometritis and, therefore, a more adequate therapeutic approach.
Cytocentrifugation and conventional methods in endometrial cytology of estrus and diestrus mares
Keywords: Cytology and uterus; Endometritis; Equine; Neutrophils